(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Renal cancer is the 13th most common malignancy globally. Cancer stem cells display progenitor cell properties such as self-renewal and ability to re-establish tumors that explain the tumor of origin. Aldehyde dehydrogenase 1 (ALDH1) has been known as a general marker of both normal stem cells and cancer stem cells. Objective :To evaluate the immunohistochemical (IHC) expression of cancer stem cell markers ALDH1 in renal cell carcinomas (RCCs). Methods: A study was designed that included 70 paraffin blocks of renal cell carcinoma tissues obtained from patients who underwent nephrectomy. The control group included 30 samples of normal renal tissue of autopsy cases from the Forensic Medicine Institute. From each two sections of 5 µm thickness were taken, one section was stained with Hematoxylin and Eosin (H&E) and the other section was immunohistochemically stained for ALDH1A1 (an isoform of ALDH1 that is expressed in the renal epithelium). Results:The difference in the IHC expression of ALDH1 is highly significant between RCC cases and control group (p4cm (p=0.023). RCC cases with renal vein invasion revealed high expression of ALDH1 (p=0.003), also ALDH1 expression increased in cases with perinephric fat invasion (p=0.014). Conclusion: ALDH1 showed higher expression in RCC tissues than normal renal tissues and it is associated with clinicopathological variables (tumor grade, tumor size, tumor stage, renal vein invasion, and perinephric fat invasion). This may reflect the role of ALDH1 in disease progression and poor prognosis of RCC. Keywords: Renal cell carcinoma, cancer stem cell marker, ALDH1, immunohistochemistry. Citation: Ahmed M. Hassan, Ban J. Qasim, Zaidoon A. Musa. Immunohistochemical expression of Aldehyde Dehydrogenase 1 (ALDH1) in renal cell carcinomas. Iraqi JMS. 2017; Vol. 15(2): 206-213. doi: 10.22578/IJMS.15.2.14